2005
DOI: 10.1186/1475-2859-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased gene expression from T7 promoters may be due to impaired production of active T7 RNA polymerase

Abstract: Background: Protein expression vectors that utilize the bacteriophage T7 polymerase/promoter system are capable of very high levels of protein production. Frequently, however, expression from these vectors does not reliably achieve optimal levels of protein production. Strategies have been proposed previously that successfully maintain high expression levels, however we sought to determine the cause of induction failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Importantly, YidC was C-terminally fused to GFP since the GFP-moiety conveniently enabled to screen already on plate for IPTG-resistant BL21(DE3)-derivatives producing YidC-GFP in the cytoplasmic membrane33. This enabled us to rapidly filter out IPTG-resistant BL21(DE3) derivatives that somehow had accumulated mutations abolishing YidC-GFP production34. Using this approach one mutant, was isolated that was not only IPTG-resistant, but also fluorescent.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, YidC was C-terminally fused to GFP since the GFP-moiety conveniently enabled to screen already on plate for IPTG-resistant BL21(DE3)-derivatives producing YidC-GFP in the cytoplasmic membrane33. This enabled us to rapidly filter out IPTG-resistant BL21(DE3) derivatives that somehow had accumulated mutations abolishing YidC-GFP production34. Using this approach one mutant, was isolated that was not only IPTG-resistant, but also fluorescent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that expression levels declined drastically in E. coli BL21 (DE3) cells containing a pET-based expression plasmid on repeated sub-culturing which could be traced to chromosomal mutations that diminished the level of functional T7 RNA polymerase. 9 A way to circumvent this problem would be to have multiple copies of the T7 RNA polymerase gene on a second plasmid as is the case with the heatinducible dual plasmid system. 10,11 We decided to investigate the stability of these dual plasmid systems by repeated sub-culturing to test their usefulness in an industrial setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, the system is not without its problems, especially a gradual decrease in the expression levels of the target gene. After several (3 to 5) subcultures, the induced expression levels may be comparable to basal expression levels, and often the host cells do not express detectable levels of the target protein [5]. This results in a lower target protein yield.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to stabilize the expression levels of the T7 p/p system, including examination of plasmid stability by lowering the uninduced T7 polymerase production levels. Another approach used freshly transformed bacteria to obtain the target protein [5-9]. However, none of these approaches have resolved the problem adequately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation